Analysing the Generative Design of Payload Part for the 3D Metal Printing - Markovits, Tamas; Daniel Eross, Laszlo; Fendrik, Armin (Communications - Scientific Letters of the University of Zilina, 2023)
Additive manufacturing provides the possibility to print complex generative designed bodies. The research deals with redesigning a payload part of a camera holder using generative design for selective laser melting. The possibility of replacing the original polymer component with a metal printed component of a greater strength and the effect of different parameters of generative design were investigated. By comparing the generative design results obtained in several phases, the goal was to find a solution that can be used to replace the previous part and become printable with 3D metal printing. The internal stress values for each case and the amount of weight reduction that can be achieved were determined. With the results obtained, the parts were prepared for printing. It is the key aspect of the industrial application of generative optimization.
Keywords: generative design; additive manufacturing; laser powder bed fusion; Ti6Al4V; weight reduction; stress analysis